The Parent Agency - David Baddiel (London : Harper Collins Children's Books, 2014)
"I wish I had better parents!" Barry said, a third time. And then suddenly the entire room started to shake... Barry Bennett hates being called Barry. In fact it's number 2 on the list of things he blames his parents for, along with 1) 'being boring' and 3) 'always being tired'. But there is a world, not far from this one, where parents don't have children. That's far too random for something so big and important. In this world, children are allowed to choose their parents. For Barry Bennett, this world seems like a dream come true. Only things turn out to be not quite that simple.